In or Out of the Men’s Movement: Subjectivity, Otherness, and Antisexist Work - Nelson, Jennifer (Canadian Journal of Education/Revue canadienne de l’éducation, 2000)
Pro-feminist men’s organizing makes advantaged, White, heterosexual men central to the movement through broader, interlocking social relations. Their relationship to White feminism, taking up of gay politics, and position vis-à-vis men of colour suggest that marginalized men are included or excluded differently on functional grounds but not always consciously as the dominant group comes to see itself as benevolent, progressive, and antisexist. Gender, race, and sexuality operate together (not individually) to secure the dominant group a central political position and a positive self-identity. Les hommes hétérosexuels, blancs et nantis occupent une place centrale dans les regroupements d’hommes proféministes en raison de leur plus vaste réseau de relations sociales. Leur lien avec le féminisme blanc, s’inspirant des droits des homosexuels, et leur position vis-à-vis des hommes de couleur semblent indiquer que les hommes marginalisés sont inclus ou exclus différemment selon des critères fonctionnels, mais pas toujours consciemment, car le groupe dominant en vient à se considérer comme bienveillant, progressiste et antisexiste. Le sexe, la race et la sexualité agissent ensemble (et non séparément) afin d’assurer au groupe do- minant une position politique centrale et une conception positive de son identité.